Analysis of Jakarta Workers Who Have Not Used Electric Cars as Daily Transportation Using the Grounded Theory Method - Taufiqillah, Rizal; Aulia, Reza Nur; Dewi, Puspita; Heikal, Jerry (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
Abstract— Transportation is a means of mobility of people or goods from one place to another. Apart from that, transportation is a means of supporting interaction activities with fellow humans. By having adequate means or means of transportation, social and economic life activities will be supported. The currently popular means of personal transportation are means of transportation powered by oil, gas, and electricity. This research aims to find out the reasons why not many workers in Jakarta use electric cars as a means of daily transportation. This research uses non-probability sampling and purposive sampling techniques. Through interviews with 15 samples of Jakarta workers who use oil-fuelled cars which were then coded and analysed, this research has explained the reasons why workers in Jakarta do not use electric cars as daily transportation. The reason is that infrastructure facilities such as SPKLU (Public Electric Vehicle Charging Stations) and special workshops for electric cars are not yet available in many places, causing workers in Jakarta to be overly concerned about using or buying electric cars.